2022
DOI: 10.21203/rs.3.rs-1327020/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunogenicity and reactogenicity of SARS-CoV-2 mRNA and inactivated vaccines in healthy adolescents

Abstract: For SARS-CoV-2 vaccines, efficacy data for BNT162b2 but not CoronaVac are available in adolescents. Phase II/III studies focused on neutralizing antibody responses in adolescents, neglecting binding antibody and cellular responses that are also important against SARS-CoV-2. Therefore, we conducted a registered clinical study (NCT04800133) to establish immunobridging with various antibody and cellular immunity markers and to compare the immunogenicity and reactogenicity of these 2 vaccines in healthy adolesce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
2
2
0
Order By: Relevance
“…When comparing vaccine effectiveness between age groups, we found people younger than 18 have a lower chance of covid-19 infection after receiving vaccines of any platform. This finding agrees with a recent immunogenicity study in children and adolescents 75. We also found that a heterologous or a homologous third dose booster can confer an equal level of protection in all age groups, even in the older group (≥65).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…When comparing vaccine effectiveness between age groups, we found people younger than 18 have a lower chance of covid-19 infection after receiving vaccines of any platform. This finding agrees with a recent immunogenicity study in children and adolescents 75. We also found that a heterologous or a homologous third dose booster can confer an equal level of protection in all age groups, even in the older group (≥65).…”
Section: Discussionsupporting
confidence: 93%
“…This finding agrees with a recent immunogenicity study in children and adolescents. 86 We also found that a heterologous or a homologous third dose booster can confer an equal level of protection in all age groups, even in the oldest age group (>65 years). If several boosters are to be administered to any age group, a heterologous or homologous regimen does not make much difference in improving immunity.…”
Section: Discussionsupporting
confidence: 53%
“…Our results are in contrast with previous observations by other groups that showed the ability of inactivated vaccines to induce both CD4 and CD8 T cell response but are however in line with other data of T cell response observed in other inactivated viral vaccines 52,53 . The difference appears to be due to the different method of analysis utilized by us and by the group in Hong-Kong 26 . The AIM assay utilized by them and by many groups worldwide (including us 29,42,54 ) is a powerful cellular technique that can define the phenotype of peptide responsive T cells.…”
Section: The Importance Of Eliciting a Multi-antigenic T Cell Respons...mentioning
confidence: 94%
“…These data suggest that inactivated vaccines might actually induce not only a weaker humoral response towards Spike but also an impaired level of T cell response which was however not experimentally supported. Analysis of SARS-CoV-2 specific T cells in individuals vaccinated with inactivated virus demonstrated the induction of T cells specific for Spike and other structural proteins (NP and Membrane) 25,26 and a magnitude of vaccine-induced CD8 T cells that were superior to the Spike-specific CD8 T cells induced by mRNA vaccines 26 . Such strong induction of CD8 T cell response was perplexing since the antigen processing and presentation pathway associated with an exogenous protein antigen like inactivated SARS-CoV-2 vaccine is expected to induce primarily a CD4 T cell response 27 .…”
Section: Introductionmentioning
confidence: 99%